Etika Berkomunikasi dalam Pandangan Hukum Pidana Isl - Usman, Usman; Syukri Azhari, Devi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Ethics in communication is a fundamental aspect of social interaction that also has legal dimensions in Islam. From the perspective of Islamic criminal law, unethical communication, such as slander, gossip (ghibah), and the spread of false information (hoaxes), may be subject to specific sanctions in accordance with the principles of justice and maqashid sharia. This study aims to examine the concept of communication ethics in Islam and its implications in Islamic criminal law. The research employs a qualitative approach through a literature review of Islamic legal sources, including the Qur'an, Hadith, and the views of fiqh scholars. The findings indicate that Islam emphasizes honest, responsible, and non-harmful communication. Several forms of communication violations that may be sanctioned under Islamic criminal law include qadzaf (false accusation of adultery without evidence), namimah (tale-bearing), and the spread of slander that damages a person's reputation. In conclusion, communication ethics in Islamic criminal law aim to uphold honor, justice, and social stability within society.